Lek fidelity and movement among leks by male Greater Sage‐grouse Centrocercus urophasianus: a capture‐mark‐recapture approach. (11th August 2014) - Gibson, Daniel; Blomberg, Erik J.; Atamian, Michael T.; Sedinger, James S.; Clark, Robert
<x xml:space="preserve">Abstract</x> Males in lek mating systems tend to exhibit high fidelity to breeding leks despite substantial evidence of skewed mating success among males. Although movements between leks are often reported to be rare, such movements provide a mechanism for an individual to improve lifetime fitness in response to heterogeneity in reproductive conditions. Additionally, estimates of apparent movements among leks are potentially biased due to unaccounted variation in detection probability across time and space. We monitored breeding male Greater Sage‐grouse Centrocercus urophasianus on 13 leks in eastern Nevada over a 10‐year period, and estimated movement rates among leks using capture‐mark‐recapture methods. We expected that male movement rates among leks would be low, despite predictions of low breeding success for most males, and that detection rates would be highly variable among leks and years. We used a robust design multistate analysis in Program mark to estimate probability of movements among leks, while accounting for imperfect detection of males. Male Sage‐grouse were extremely faithful to their leks; the annual probability of a male moving away from its original lek of capture was approximately 3% (se = 0.01). Detection probabilities varied substantially among leks (range = 0.21–0.95), and among years (range = 0.30–0.76), but remained relatively constant within years at each lek. These results suggest that male Sage‐grouse dispersal is either rare, or consists primarily of dispersal of sub‐adults from their natal areas prior to the breeding season. The study highlights the benefits of robust design multistate models over standard 'live‐encounter' analyses, as they not only permit estimation of additional parameters, such as movement rates, but also allow for more precise parameter estimates that are less sensitive to heterogeneity in detection rates. Additionally, as these data were collected using capture‐mark‐recapture methods, our approach to estimating movement rates would be beneficial in systems where radiotagging is detrimental to the study organism.